Volatility and Growth: An Explanation for the Disagreement (2013)
This paper reconsiders the e_ects of volatile growth rates on growth itself. I show that the underlying endogeneity of government size can hide the net growth e_ects from volatility. There exists a positive direct and a negative indirect channel, with the latter operating through the size of the public sector. Risk-averse citizens respond to volatility either with precautionary savings (direct e_ect) or by demanding a stronger public safety net, which in turn lowers growth (indirect e_ect). However, the indirect channel is only available if the political regime allows citizens to determine their desired level of public services. I test this theory on a balanced panel of 95 countries from 1960 { 2010. The paper reveals the latent endogeneity of government size in a single growth equation framework and o_ers a simultaneous estimation method as an alternative. Results support the existence of both effects. The direct channel is stronger in autocratic societies, but as a country turns to democracy the indirect channel dominates. Volatility has a positive net e_ect on growth in autocratic nations, but a negative net effect in democratic societies. This finding explains why previous growth analyses of volatility at times reached contradicting conclusions.